Determinan Perilaku Menyusui dengan Keberhasilan ASI Eksklusif di Wilayah Kerja Puskesmas Menteng Kota Palangka Raya - Arisani, Greiny; Sukriani, Wahidah (Window of Health : Jurnal Kesehatan, 2020)
Exclusive breast milk is breast milk that is given to babies from birth for 6 months without adding or replacing with other food or drinks. Exclusive breastfeeding acts as the first immunization, protection from respiratory infections, diarrhea and other potentially life-threatening diseases. One factor that contributes to the low success rate of exclusive breastfeeding globally is socio-cultural factors related to breastfeeding behavior. The purpose of this study was to analyze the determinants of breastfeeding behavior (predisposing factors, enabling factors and reinforcing factors) with the success of exclusive breastfeeding. Observational analytic research method with design cross sectional. The results of this study were 61% not exclusive breastfeeding. Then the test results chi square on predisposing factors including work, attitude and knowledge significantly related to the success of exclusive breastfeeding. Enabling factors including birth attendants, birthplace and history of early breastfeeding initiation (IMD) have a significant relationship with the success of exclusive breastfeeding and reinforcing factors on family support variables are significantly related to the success of exclusive breastfeeding. The logistic regression test results concluded the history of early breastfeeding initiation (IMD) variables (p = 0.001; OR = 16.625) dominant variable with the success of exclusive breastfeeding along with family support variables (p = 0.013; OR = 6.791), occupation (p = 0.014; OR = 3,689), knowledge (p = 0.027; OR = 6.892) and birth attendants (p = 0.047; OR = 6.604).